2012
DOI: 10.1111/j.1537-2995.2012.03575.x
|View full text |Cite
|
Sign up to set email alerts
|

Current information on the immunologic status of occult hepatitis B infection

Abstract: Hepatitis B is one of the most frequently occurring posttransfusion infections. Occult hepatitis B (OB) is a form of hepatitis B in which, despite the presence of hepatitis B virus (HBV) DNA in the serum and hepatocytes of a carrier, hepatitis B surface antigen is absent. In addition to the risk of transfusion of infection, OB can lead to cirrhosis, hepatic cancer, and reactivation of the viral duplication process in the carrier. The mechanisms responsible for progression of OB are yet to be clarified; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
0
27
0
4
Order By: Relevance
“…Moreover, another study showed a similar response in terms of overexpression of interleukins IL-10, IL-17 and IFN-gamma, while IL-12 and stromal cell-derived factor (SDF)-1alpha presented no difference in OBI patients when compared to healthy subjects who were clear of HBV infection [73,74,75]. Patients with OBI seem to be unable to express high levels of IL-12 and SDF-1alpha, a fact that could facilitate clearing of HBV through activation and migration of T lymphocytes and NK cells [76] (Figure 2). A related study found a decrease in CD8+ T cells in individuals with OBI, compared to healthy individuals [76].…”
Section: Principal Molecular Mechanisms Associated With Obimentioning
confidence: 99%
“…Moreover, another study showed a similar response in terms of overexpression of interleukins IL-10, IL-17 and IFN-gamma, while IL-12 and stromal cell-derived factor (SDF)-1alpha presented no difference in OBI patients when compared to healthy subjects who were clear of HBV infection [73,74,75]. Patients with OBI seem to be unable to express high levels of IL-12 and SDF-1alpha, a fact that could facilitate clearing of HBV through activation and migration of T lymphocytes and NK cells [76] (Figure 2). A related study found a decrease in CD8+ T cells in individuals with OBI, compared to healthy individuals [76].…”
Section: Principal Molecular Mechanisms Associated With Obimentioning
confidence: 99%
“…OBI may maintain these direct mechanisms of HBV-related carcinogenesis, such as the ability to be integrated into the host genome and production of transforming proteins, mainly including X and preS-S proteins 11,32,39-41. In contrast, OBI may also exert pro-oncogenic properties through indirect mechanisms.…”
Section: Mechanism Of Carcinogenesis In Patients With Obimentioning
confidence: 99%
“…In contrast, OBI may also exert pro-oncogenic properties through indirect mechanisms. These are associated with its propensity to induce persistent necroinflammation in the liver and to promote progression of chronic hepatitis to liver cirrhosis, which indicates the step preceding HCC occurrence in the majority of cases 11,20-22,25,26,41. Furthermore, indirectly, continuous HBV replication caused by OBI can mediate alterations in transforming growth factor-β1 and α2-macrogloblin production, leading to liver carcinogenesis 42…”
Section: Mechanism Of Carcinogenesis In Patients With Obimentioning
confidence: 99%
“…Immune responses are the main defense against tumors and infectious diseases [1,2]. Uncontrolled immune responses against self and foreign antigens are described as autoimmunity and hypersensitivity, respectively [3].…”
Section: Introductionmentioning
confidence: 99%